The question of privacy in the context of information science: an analysis of theses and dissertations of the Postgraduate Program in Information Science of UNESP Campus Marilia - Grisoto, Ana Paula [UNESP]; Goncalves Sant'Ana, Ricardo Cesar [UNESP]; Santarem Segundo, Jose Eduardo [UNESP] (Univ Brasilia, Dept Ciencia Informacao, 2015)
With the increased use of information and communication technologies, there is the concern about privacy, due to excessive or improper use of information and data of individuals, reflecting the need for studies and discussions on the topic. Thus, this research has the objective to identify the occurrence of the subject privacy in the corpus of theses and dissertations of the Graduate Program in Information Science (PPGCI) of UNESP/Marilia, aiming to highlight the theme of incipient in IC and display an overview of productions that discuss the topic. Therefore, it performed the literature on privacy and Information Science and delimited that the empirical field for the collection of information would be the scientific production of PPGCI UNESP/Marilia, Indexed Institutional Repository UNESP. The criteria for the search term privacy were the title, abstract, keywords and text. It was found initially scarcity of publications in the CI in developing the theoretical framework and the study corroborated to show that there is a fairly long way to go as regards discussions and studies on privacy, especially in relation to the Information Science, due to low number of papers that discuss in depth the issue of privacy in PPGCI UNESP/Marilia.
Keywords: Information and Communication Technologies; Information security; Private data; Right to privacy